Pengaruh Latihan Plyometric dan Lompat Gawang untuk Meningkatkan Kemampuan Jumping Smash pada Siswa Ekstrakulikuler Bola Voli Putri SMP Negeri 2 Karanggayam - Junianto, Heri Is; widodo, Puput (Jurnal Kridatama Sains dan Teknologi, 2023)
This study aims to determine: 1) is there an effect of plyometric jump exercise on the female volleyball athlete's jumping smash at SMP Negeri 2 Karanggayam, 2) is there an effect of goal-jumping exercise on the extracurricular female volleyball athlete's jumping smash at SMP Negeri 2 Karanggayam, 3) the type of exercise used more effective against the jumping smash of female volleyball athletes at SMP Negeri 2 Karanggayam. This research is an experiment with the research design used is "two groups pretest-posttest design". The instrument in this study was a jumping smash test with a reliability of 0.99 and a validity of 0.989. The subjects in this study were Extracurricular Girls Volleyball Athletes at SMP Negeri 2 Karanggayam, totaling 12 athletes. The data analysis technique used t test with a significance level of 5%.The results of the study concluded that: 1) there was no effect of plyometric jump training on the jumping smash of extracurricular volleyball athletes at SMPN 2 Karanggayam with t count (1.608) > t table (2.201), and the significance value of p (0.136) < 0.05, with percentage increase of 0.07% or 2.75 cm. 2) there is an effect of hurdles training on the jumping smash of extracurricular volleyball athletes at SMPN 2 Karanggayam with t count (3.616) > t table (2.201), and p-value (0.004) < 0.05, these results indicate that the t-count value is more greater than t table. 3) with an increase of 0.13% or 5 cm. The goal jump exercise is better for improving the jumping smash of extracurricular volleyball athletes at SMPN 2 Karanggayam. It is calculated from the difference in the average difference that the average post-test difference in the plyometric jump group is 3.08cm, the post-test average value for the hurdles group is 3.08cm. 5 cm, seen from the difference in the post-test value of 1.95 cm.Keywords: Plyometric Exercise, goal jump exercise, Jumping smash